Fungsi Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Serta Implikasinya Terhadap Kompetensi Lulusan SMA - Suhaya Suhaya (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2016)
The purpose of this study was to analyze the function of the principal's leadership on teacher performance implications for high school students graduate competencies Tangerang Banten Province. The research method is descriptive and verification. Descriptive method using assessment scores on the study variables. Descriptive analysis used single cross-sectional design that describes and illustrates the perception of teachers on the leadership of the principal. Whereas analysis verification used to verify the validity of the proposed research hypotheses. The unit analysis in this study is a high school teacher in the town and district Tangeran Tangerang Banten Province. There are a total of 55 high schools and 208 private high school. Sampling technique using simple random sampling, the total sample of 216 respondents. The results can be summarized as follows: 1) The principal function as principals include educator, manager, administrator, supervisor, leader, innovator and motivator, significantly affect the performance of teachers either partially or simultaneously in a high school Tangerang Banten Province , 2) the performance of teachers significantly influence a high school grad in Tangerang Banten Province.